2(5-3x)=3(4x+1)

Simple and best practice solution for 2(5-3x)=3(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5-3x)=3(4x+1) equation:


Simplifying
2(5 + -3x) = 3(4x + 1)
(5 * 2 + -3x * 2) = 3(4x + 1)
(10 + -6x) = 3(4x + 1)

Reorder the terms:
10 + -6x = 3(1 + 4x)
10 + -6x = (1 * 3 + 4x * 3)
10 + -6x = (3 + 12x)

Solving
10 + -6x = 3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
10 + -6x + -12x = 3 + 12x + -12x

Combine like terms: -6x + -12x = -18x
10 + -18x = 3 + 12x + -12x

Combine like terms: 12x + -12x = 0
10 + -18x = 3 + 0
10 + -18x = 3

Add '-10' to each side of the equation.
10 + -10 + -18x = 3 + -10

Combine like terms: 10 + -10 = 0
0 + -18x = 3 + -10
-18x = 3 + -10

Combine like terms: 3 + -10 = -7
-18x = -7

Divide each side by '-18'.
x = 0.3888888889

Simplifying
x = 0.3888888889

See similar equations:

| 12+5b=-2b-5b | | -top-4=to | | F(1)=3x^2-7 | | 3x+6y+1=10 | | 9f^2+f=0 | | 9u=3 | | 1.4(2.5x-2.8y)-3.5(2.0x+1.5y)= | | 1-5x=1-3x-3x | | -6p^2-2p+9=0 | | Z=4c/n | | a-45=20 | | 3x+46=-13x-6-10x | | (5/6)b=1(7/8) | | 2t-3x+6x-y= | | 4m-5=2m+20 | | H=-16t^2+4t+2 | | 76=4-12e | | -2j^2+8j+8=0 | | -7x+30=-2x | | 5x+8=7x-36 | | 6x-24=35 | | 2j^2+8j+8=0 | | -8k-2k=4-2k-4k | | 294630872364059723649582683475623847562984562845694856238945623894562389475628374562837456834756284756298347562893475623894756283475628347562384756238947563456=1 | | .75x=169.95 | | -2x-12=-6x-4 | | (X-1)+(x-1)= | | 9m-8=5m+4 | | 20+35+x=90 | | 7/2n-21=0 | | t-6t=-13+t-(-3) | | 6a-6=-7a+5+2a |

Equations solver categories